CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17